Oxygen Supply to the Tropical North East Atlantic Oxygen Minimum Zone - Hahn, Johannes; Fischer, Tim; Brandt, Peter; Greatbatch, Richard John; Körtzinger, Arne; Tanhua, Toste; Visbeck, Martin; Banyte, Donata; Dengler, Marcus; Krahmann, Gerd (2014)
Diapycnal and meridional oxygen supply pathways into the Tropical North East Atlantic Oxygen Minimum Zone (TNEA OMZ) are quantified using a comprehensive observational data set of microstructure measurements, moored observations and repeat ship sections that were carried out in the TNEA during the recent decade. Referring to a state-of-the-art estimate of oxygen consumption, an oxygen budget for the TNEA OMZ is derived. At the OMZ core depth, diapycnal mixing and meridional eddy mixing can account for most of the oxygen supply that is needed to balance the oxygen consumption. In contrast, above the OMZ core depth (100m – 400m) most of the oxygen supply remains unexplained, which is likely balanced by mean zonal advection.